Cellular Functions and Molecular Mechanisms of the ESCRT Membrane-Scission Machinery. Issue 1 (January 2017) - Christ, Liliane; Raiborg, Camilla; Wenzel, Eva M.; Campsteijn, Coen; Stenmark, Harald
Abstract : The endosomal sorting complex required for transport (ESCRT) machinery is an assembly of protein subcomplexes (ESCRT I-III) that cooperate with the ATPase VPS4 to mediate scission of membrane necks from the inside. The ESCRT machinery has evolved as a multipurpose toolbox for mediating receptor sorting, membrane remodeling, and membrane scission, with ESCRT-III as the major membrane-remodeling component. Cellular membrane scission processes mediated by ESCRT-III include biogenesis of multivesicular endosomes, budding of enveloped viruses, cytokinetic abscission, neuron pruning, plasma membrane wound repair, nuclear pore quality control, nuclear envelope reformation, and nuclear envelope repair. We describe here the involvement of the ESCRT machinery in these processes and review current models for how ESCRT-III-containing multimeric filaments serve to mediate membrane remodeling and scission. Trends: The ESCRT machinery is an evolutionarily conserved machinery for scission of membrane necks from their interior. The ESCRT machinery is a modular system consisting of three subcomplexes named ESCRT-I, -II, and -III. The first two complexes function mainly in protein sorting and in recruitment of ESCRT-III, together with Bro1-domain containing proteins. By contrast, the ESCRT-III complex coordinates the membrane-severing function. The ESCRT machinery is recruited to sites of action by subfunction-specific targeting modules. These factors include ESCRT-0 (MVE formation), CEP55 (cytokinesis), and Gag (virus budding), that are able to associate with ESCRT components and Bro1-domain proteins. ESCRT-III subunits assemble into helical filaments that mediate membrane deformation and scission, in cooperation with the ATPase VPS4.